Prosthetic-Driven Autotransplantation with the Assistance of Medical Image-Processing Software and a Real-Time Navigation System: A Case Report. - Hung-Ming Chang; Hui-Hsin Ko; Chih-Wen Chi; Yi-Ting Deng; I-Ping Lin; Szu-Han Chen (International Journal of Periodontics & Restorative Dentistry)
Autotransplantation has been proven as a viable method of reconstructing missing teeth. While preparing the recipient site, the bone reduction location depends largely on the surgeon's experience. Inappropriate overpreparation can cause biologic and esthetic complications, such as buccal or lingual bone resorption. This paper provides an innovative method to aid clinicians in precisely preparing a recipient site with the assistance of medical image-processing software and a real-time navigation system. This case report presents the autotransplantation of a mandibular molar using this technique with good short-term (6 months) clinical outcomes, including radiographic bone fill, normal probing pocket depth, physiologic tooth mobility, acceptable gingival level, and satisfactory restoration.